De lege ferenda postulates concerning the provision of Article 75c of the Banking Law - Maciaczyk, Michał (Studia Iuridica Toruniensia, 2025)
The subject of the discussion is the analysis of issues related to the termination of credit agreements under Article 75c of the Banking Law. The article presents key issues that have sparked controversy in legal doctrine and case law, and proposes de lege ferenda postulates aimed at clarifying the regulation and strengthening the protection of borrowers.